Analisis Dan Perancangan Sistem Informasi Reservasi Gedung Dan Penginapan Pada Kantor LPMP Jambi - Dioputra, Sepryhatin; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2020)
Puts more values on its building and the facilities to increase the non-tax state revenue (PNBP). Previously, At the Institution of Quality Assurance on Education (LPMP) of Jambi Province used the building and facilities as the venue for conducting their own internal programs. As the external demand increases, LPMP has made policies and decided to open its building and facilities for public by setting low and reasonable price. data processing leases for Buildings and Lodging is done manually, the manual process is felt to give less convenience in its implementation, booking lodging or building facilities manually slow the running procedures, online-based information systems are felt will be more helpful in processing data processing leases for Buildings and Lodging in Jambi LPMP Office, with the online database based method of a reservation information system design can make it easier for the manager and customer to access the Building and Lodging needed.